2017
DOI: 10.1038/mp.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine-induced reduction in mGluR5 availability is associated with an antidepressant response: an [11C]ABP688 and PET imaging study in depression

Abstract: The mechanisms of action of the rapid antidepressant effects of ketamine, an NMDA glutamate receptor antagonist, have not been fully elucidated. This study examined effects of ketamine on ligand binding to a metabotropic glutamatergic receptor (mGluR5) in individuals with major depressive disorder (MDD) and healthy controls. Thirteen healthy and thirteen MDD nonsmokers participated in two [11C]ABP688 positron emission tomography (PET) scans on the same day – before and during intravenous ketamine administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 78 publications
(99 reference statements)
6
82
0
Order By: Relevance
“…Several other studies have shown that antagonism of mGluR5 (18,37,38) and genetic deletion of mGluR5 (39) block or reduce fear conditioning and that fear conditioning is associated with increased expression of mGluR5 (18). Furthermore, a wealth of research shows that mGluR5 antagonists have anxiolytic effects in animal models (10-15), and we recently showed that down-regulating mGluR5 is associated with a decrease in anxiety symptoms in individuals with major depressive disorder (MDD) (40). The correlation between mGluR5 availability and avoidance symptoms suggests that mGluR5 could be a symptom-specific target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have shown that antagonism of mGluR5 (18,37,38) and genetic deletion of mGluR5 (39) block or reduce fear conditioning and that fear conditioning is associated with increased expression of mGluR5 (18). Furthermore, a wealth of research shows that mGluR5 antagonists have anxiolytic effects in animal models (10-15), and we recently showed that down-regulating mGluR5 is associated with a decrease in anxiety symptoms in individuals with major depressive disorder (MDD) (40). The correlation between mGluR5 availability and avoidance symptoms suggests that mGluR5 could be a symptom-specific target.…”
Section: Discussionmentioning
confidence: 99%
“…Venous samples were acquired at 15,20,25,30,40,50,60,75,90,105, and 120 min postinjection for calculation of a metabolite-corrected venous input function as validated previously (19). A 6-min transmission scan was obtained for attenuation correction.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, secondary or complementary changes in metabotropic glutamate receptor function may be intimately involved (or respond) to the synaptic pathophysiology that underlies functional disconnections. This is suggested by imaging studies that show, for example, reduced glutamate receptor 5 (mGluR5) density in major depression and response to antidepressant treatment …”
Section: Future Stepsmentioning
confidence: 99%
“…This is suggested by imaging studies that show, for example, reduced glutamate receptor 5 (mGluR5) density in major depression and response to antidepressant treatment. 125,126 It is worth emphasizing that although the interactions among…”
Section: Future S Tepsmentioning
confidence: 99%
“…Throughout the brain, these receptors are involved in regulating glutamatergic neurotransmission and synaptic plasticity, contributing to associative learning and memory (Anwyl, ; Ayala et al, ). mGluR5 alterations are linked to a range of psychiatric and neurological disorders (Davis, Holmes, Pietrzak, & Esterlis, ; Esterlis et al, ; Scharf, Jaeschke, Wettstein, & Lindemann, ; Smart, Scala, El Mestikawy, Benkelfat, & Leyton, ), while drugs targeting the radioligand binding site are being investigated for diverse conditions, including substance use disorders, fragile X syndrome, and levodopa‐induced dyskinesia in Parkinson's disease (Caprioli, Justinova, Venniro, & Shaham, ; Haass‐Koffler et al, ; Tison et al, ; Youssef et al, ). The ligand also has applications in drug development to estimate occupancy at the modulatory site (Kågedal et al, ; Mathews et al, ).…”
Section: Introductionmentioning
confidence: 99%